Comparing the central arterial stiffness indices in the decompensated and compensated states of heart failure: a cohort study. (14th October 2021) - Youssef, G; El Fol, A; Ammar, W; Sharaf, Y
Abstract: Background: Arterial stiffness is strongly linked to the pathogenesis of heart failure (HF), and development of acute decompensation of patients with stable chronic HF. Purpose: To compare the arterial stiffness indices in patients with heart failure with reduced ejection fraction (HFrEF) during hospitalization with acute decompensated state, and then three months later after discharge during the compensated state. Methods: One hundred patients with acute decompensated HFrEF (NYHA class III and IV) and left ventricular ejection fraction (LVEF) ≤35% were included in the study. Fifty-six patients (56%) had ischemic cardiomyopathy (ICM) and the rest had dilated cardiomyopathy (DCM). During the initial and follow up visits, all patients were subjected to full medical history taking, clinical examination, electrocardiography (ECG), transthoracic echocardiography (TTE), routine labs and non-invasive pulse wave analysis (PWA) by the Mobil-O-Graph 24h PWA device for measurement of arterial stiffness parameters. Results: The mean age was 51.6±6.1 years and 80% were males. There was a significant reduction of the central arterial stiffness indices in patients with HFrEF during the compensated state as compared to their decompensated state values, table (1). During the decompensated state, patients with ICM showed a significantly higher PWV as compared to patients with DCM (9.2±1.1 vs 8.6±1.4 m/sec, P=0.042), patients presented with NYHA FC IV (n=64) showed higher AI (24.5±10.0 vs 16.8±8.6, p<0.001) and PWV (9.2±1.3 vs 8.5±1.2, p=0.021) than patients with NYHA FC III, and despite the relatively smaller number of females, they showed higher stiffness indices than males, table (2). Conclusion: Central arterial stiffness indices derived from the non-invasive Mobil-O-Graph 24h PWA device in patients with HFrEF were significantly lower in the compensated state as compared to the decompensated state. Patients with ICM, NYHA FC IV and females showed higher stiffness indices in their decompensated state of heart failure. Funding Acknowledgement: Type of funding sources: None.